Improving carrier transport in Cu2O thin films by rapid thermal annealing. (24th January 2018) - Bergum, Kristin; Riise, Heine N; Gorantla, Sandeep; Lindberg, Per F; Jensen, Ingvild J T; Gunnæs, Anette E; Galeckas, Augustinas; Diplas, Spyros; Svensson, Bengt G; Monakhov, Edouard
Abstract: Cuprous oxide (Cu2 O) is a promising material for large scale photovoltaic applications. The efficiencies of thin film structures are, however, currently lower than those for structures based on Cu2 O sheets, possibly due to their poorer transport properties. This study shows that post-deposition rapid thermal annealing (RTA) of Cu2 O films is an effective approach for improving carrier transport in films prepared by reactive magnetron sputtering. The as-deposited Cu2 O films were poly-crystalline, p -type, with weak near band edge (NBE) emission in photoluminescence spectra, a grain size of 100 nm and a hole mobility of 2–18 cm 2 V −1 s −1 . Subsequent RTA (3 min) at a pressure of 50 Pa and temperatures of 600–1000 °C enhanced the NBE by 2–3 orders of magnitude, evidencing improved crystalline quality and reduction of non-radiative carrier recombination. Both grain size and hole mobility were increased considerably upon RTA, reaching values above 1 µ m and up to 58 cm 2 V −1 s −1, respectively, for films annealed at 900–1000 °C. These films also exhibited a resistivity of 50–200 Ω cm, a hole concentration of 10 15 cm −3 at room temperature, and a transmittance above 80%.